Access to justice and entrepreneurship: Evidence from Brazil's special civil tribunals - Guilherme Lichand; Rodrigo R. Soares (Institute for the Study of Labor (IZA), 2011)
Entrepreneurship is usually identified as an important determinant of aggregate productivity and long-term growth. The determinants of entrepreneurship, nevertheless, are not entirely understood. A recent literature has linked entrepreneurship to the development of the justice system. This paper contributes to this literature by evaluating the role of access to justice in determining the incidence of entrepreneurship. We explore the creation of Special Civil Tribunals in the Brazilian state of S\~ao Paulo during the 1990s. Special Civil Tribunals increased the geographic presence of the justice system, simplified judicial procedures, and increased the speed of adjudication of disputes. Using census data, and difference-in-differences and instrumental variable strategies, we find that implementation of Special Civil Tribunals led to increased entrepreneurship, defined as the probability that individuals are employers or self-employed. Results are particularly strong and robust for the case of self-employment, and do not seem to be related to other changes in infrastructure or public good provision at the local level, or to pre-existing trends in entrepreneurship.
urn:nbn:de:101:1-20110927201
Keywords: K1; K41; K42; H41; O12; O17; O54; 330; access to justice; courts; entrepreneurship; institutions; Brazil